Preoperative prealbumin and transferrin: Relation to 30-day risk of complication in elective spine surgical patients. Issue 9 (March 2019) - Takemoto, Erin; Yoo, Jung; Blizzard, Sabina R.; Shannon, Jackilen; Marshall, Lynn M.
Abstract: Summary of Background Data: There is growing interest in identifying nutritional biomarkers associated with poor outcomes of elective spine surgery. Prealbumin and transferrin are both biomarkers of nutritional status that can be obtained from clinical laboratories. However, associations of preoperative measures of these nutritional biomarkers across their range with risk of complications from spine surgery have not been fully investigated. Objective: Determine associations of preoperative prealbumin and transferrin levels with 30-day risk of complication among elective spine surgery patients. Study Design: Cohort study with preoperative prealbumin and transferrin collected as standard of care. Outcome Measures: 30-day risk of medical complication. Methods: Data were obtained from medical records of 274 consecutive adult patients ages ≥50 years who underwent elective spine surgery from June 2013 to June 2014. Prealbumin (mg/dL), serum transferrin (mg/dL), and preoperative factors were abstracted from medical records. Prealbumin and transferrin levels were categorized into quartiles and as below versus median or higher. The primary outcome measure was 30-day risk of medical complication, such as renal failure or infections. Associations of the biomarkers with outcome risk were assessed with chi-square tests and with risk ratios (RR) and 95% confidence intervals (CI) estimated with multivariable log-binomial regression. Results: The 274 adults studied had a median prealbumin level of 27.4 mg/dL and a median transferrin level of 265.0 mg/dL. The 30-day risk of complication was 12.8% (95% CI: 8.8%–16.7%). Risk of complication did not vary by quartile for either prealbumin ( P = .26) or transferrin ( P = .49) and was not associated either with prealbumin (below median, RR = 1.1, 95% CI: 0.8, 1.5) or transferrin (below median, RR = 1.1, 95% CI: 0.8, 1.6). Conclusions: Among adults undergoing elective spine surgery, the 30-day risk of complication was not associated with prealbumin or transferrin. Nutrition status, as measured by prealbumin and transferrin, does not appear to be associated with complication risk. Level of evidence: Level III. Abstract : Supplemental Digital Content is available in the text